A Cohort Study of Adult Patients with Severe Dengue in Taiwanese Intensive Care Units: The Elderly and APTT Prolongation Matter for Prognosis. - Chih-Cheng Hsieh; Cong-Tat Cia; Jen-Chieh Lee; Junne-Ming Sung; Nan-Yao Lee; Po-Lin Chen; Te-Hui Kuo; Jo-Yen Chao; Wen-Chien Ko (PLoS Neglected Tropical Diseases, 2017)
There was a large dengue outbreak in Taiwan in 2015, in which the ages of the affected individuals were higher than those in other countries. The aim of this study was to explore the characteristics and prognostic factors for adults with severe dengue in intensive care units (ICUs).All adults admitted to ICUs with dengue virus infection (DENV) at a medical center from July 1, 2015 to December 31, 2015 were enrolled. DENV was diagnosed by the presence of serum NS1 antigen, IgM antibodies to dengue virus, or dengue virus RNA by real-time reverse transcriptase polymerase chain reaction. Demographic data, clinical features, and lab data were collected, and a multivariate Cox model was used to identify the predictive factors for in-hospital mortality.Seventy-five patients admitted to ICUs with laboratory-confirmed DENV were enrolled (mean age 72.3±9.3 years). The most common comorbidities included hypertension (72.0%), diabetes (43.7%), and chronic kidney disease (22.7%). The in-hospital case fatality rate (CFR) was 41.3%. The patients who died were predominantly female, had higher disease severity at ICU admission, shorter ICU/hospital stay, longer initial activated partial thromboplastin time (APTT), and higher initial serum aspartate transaminase levels. Cardiac arrest before ICU admission (hazard ratio [HR]: 6.26 [1.91-20.54]), prolonged APTT (>48 seconds; HR: 3.91 [1.69-9.07]), and the presence of acute kidney injury on admission (HR: 2.48 [1.07-5.74]), were independently associated with in-hospital fatality in the Cox multivariate analysis.During the 2015 dengue outbreak in Taiwan, the patients with severe dengue in ICUs were characterized by old age, multiple comorbidities, and a high CFR. Organ failure (including cardiac failure, and renal failure) and coagulation disturbance (prolongation of initial APTT) were independent predictive factors for in-hospital fatality.